KEANEKARAGAMAN JENIS ANGGREK PULAU WAWONII - Diah Sulistiarini (The East Java Biological Society, 2008)
An exploration and inventory of orchid plant was carried out in Wawonii Island, South-east Celebes. The aim of the study was to know about orchid diversity in the area, because no fi eld survey conducted since 1940. For that reason all orchid species fi nding were collected as life collection for planted in the Bogor Botanical Garden and dried collection for stored in the Herbarium Bogoriense. Ninety one orchid species were recorded and 36 species of them were new record of Celebes. Out of 1 species Trichoglottis javanica J. J. Sm. was recognized as endemic of Java. Five species orchid were endemic in Celebes, there are Bulbophyllum balapiuense J.J.Sm., Hyppeophyllum celebicum Schltr., Oberonia exaltata Schltr., Thrixspermum celebicum Schltr. and Malaxis lombasangensis (J.J.Sm.) S. Thomas Schut. & de Vogel.